The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1071/an10106
|View full text |Cite
|
Sign up to set email alerts
|

Managing for rainfall variability: long-term profitability of different grazing strategies in a northern Australian tropical savanna

Abstract: Several grazing strategies are recommended to manage sustainably for rainfall variability in northern Australia, but there is little objective data on their profitability relative to less sustainable management systems such as heavy stocking. In 1997, a large cattle grazing trial was initiated in northern Queensland to quantify the relative performance of a range of grazing strategies in a variable climate. These strategies were (i) moderate stocking (MSR) stocked at the calculated long-term carrying capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 35 publications
4
57
0
Order By: Relevance
“…Ideally, given the marked influence climate has on pasture and livestock outcomes (Jones et al 1995;O'Reagain et al 2011), the length of the experimental period for farming systems research should be sufficient to allow adequate representation of the expected range of climatic conditions (Walker 1988). This would enable sufficient demonstration of treatment responses and would reduce the need for assumptions or modelling to extrapolate responses to climatic conditions for which there are no data to support calibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, given the marked influence climate has on pasture and livestock outcomes (Jones et al 1995;O'Reagain et al 2011), the length of the experimental period for farming systems research should be sufficient to allow adequate representation of the expected range of climatic conditions (Walker 1988). This would enable sufficient demonstration of treatment responses and would reduce the need for assumptions or modelling to extrapolate responses to climatic conditions for which there are no data to support calibration.…”
Section: Discussionmentioning
confidence: 99%
“…climatic records over the long term (Laws et al 2000;O'Reagain et al 2011). Climate is especially important when the treatments being evaluated, such as changes in soil fertility and botanical composition, are known to take many years to reach equilibrium (Walker 1988;Jones et al 1995).…”
mentioning
confidence: 99%
“…A local impact of intense low-pressure systems, including cyclones, is the combination of intense rainfall and high wind speeds, which causes lodging and reduction of sugar content in sugarcane (Singh et al 2002) and, potentially, damage to plantation forests. Northern inland pasture systems are generally favoured by La Niña events (Park et al 2003) and could respond positively to climate change in terms of productivity, albeit with a need to buffer production between years of high and low rainfall (O'Reagain et al 2011). Any increase in growing season temperature or in high-temperature events will affect the dynamics of production, but adaptation can be implemented through pasture and animal management .…”
Section: Systems Of Cultivated Plant Species and Relative Production mentioning
confidence: 99%
“…In a study of different grazing strategies in northern Queensland, O'Reagain et al (2011) found that, under variable climatic conditions, the best financial and sustainable outcomes over the long term were achieved through a variable stocking strategy that allowed the adjustment of stocking rate early in each dry season. Such a system is similar to the flexible grazing management employed on farmlets A and B in the present experiment.…”
Section: Integrative Discussionmentioning
confidence: 99%